A time-domain feedback calibration method for air-coil magnetic sensor. (March 2019) - Wang, Haowen; Fu, Zhihong; Wang, Yao; Tai, Hengming; Qin, Shanqiang; Liao, Xian
Highlights: The proposed calibration scheme saves time for signal acquisition. Only need to collect the output signal to complete the calibration of the device. High calibration accuracy and controllable error by feedback signal. Abstract: An air-coil sensor (ACS) is a type of induction magnetometer used to measure the variation of a magnetic field. Due to the limited bandwidth of the coil, its output signal is distorted, a phenomenon known as the transition process. To measure the magnetic field accurately, the relationship must be confirmed by calibration. However, conventional methods require a uniform magnetic field with various frequencies to ensure the induced electromotive force is controllable. The time taken to acquire the signal correlates with the number of test frequencies, and the equipment used to generate the uniform magnetic field must be tailored to the shape of the ACS under test. This paper proposes a time-domain feedback calibration method for ACS to avoid the above constraints. An algorithm is applied to relieve the dependence of the calibration file on the input signal, so that the calibration file will not be affected by the calculation error of the input signal nor be limited by the uniform magnetic field, and the accuracy of the calibration file can be evaluated by the feedback signal. The exponential current, which contains a variety of frequency components, is selected as the calibration signal to shorten the time of data collection. The equipment used to generate the calibration signal is simple, which is suitable for on-site calibration. The scheme can be used for rapid calibration of various air-core coils, and provides a better solution for realizing embedded self-test of ACS.